Artificial Life and Computational Intelligence : First Australasian Conference, ACALCI 2015, Newcastle, NSW, Australia, February 5-7, 2015. Proceedings - Chalup, Stephan K.; Blair, Alan D.; Randall, Marcus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the First Australasian Conference on Artificial Life and Computational Intelligence, ACALCI 2015, held in Newcastle, NSW, Australia, in February 2015. The 34 revised full papers presented were carefully reviewed and selected from 63 submissions. The papers are organized in the following topical sections: philosophy and theory; game environments and methods; learning, memory and optimization; and applications and implementations.
ALife Using Adaptive, Autonomous, and Individual Agent Control -- Computational Understanding and Manipulation of Symmetries -- Ontological and Computational Aspects of Economic-Environmental Modelling -- Exploring the Periphery of Knowledge by Intrinsically Motivated Systems -- On the Estimation of Convergence Times to Invariant Sets in Convex Polytopic Uncertain Systems -- A Sensor Fusion Approach to the Fault Tolerant Control of Linear Parameter Varying Systems -- Emotions and Their Effect on Cooperation Levels in N-Player Social Dilemma Games -- Agent-Based Simulation of Stakeholder Behaviour through Evolutionary Game Theory -- Evolving Cellular Automata for Maze Generation -- Point of Regard from Eye Velocity in Stereoscopic Virtual Environments Based on Intersections of Hypothesis Surfaces -- Formalising Believability and Building Believable Virtual Agents -- Gamification for Education: Designing a Pharmacy Education Game -- Sound Improves Player Performance in a Multiplayer Online Battle Arena Game -- Generic Construction of Scale-Invariantly Coarse Grained Memory -- Transgenic Evolution for Classification Tasks with HERCL -- Learning Nursery Rhymes Using Adaptive Parameter Neurodynamic Programming -- Autonomous Hypothesis Generation as an Environment Learning Mechanism for Agent Design -- Learning Options for an MDP from Demonstrations -- A Grammarless Language Generation Algorithm Based on Idiotypic Artificial Immune Networks -- Evolving Unipolar Memristor Spiking Neural Networks -- A Genetic Algorithm Solver for Pest Management Control in Island Systems -- An Evolutionary Algorithm for Deriving Withdrawal Rates in Defined Contribution Schemes -- Evolving Point Packings in the Plane -- The Effect of Reactant and Product Selection Strategies on Cycle Evolution in an Artificial Chemistry -- Use of a High-Value Social Audience Index for Target Audience Identification on Twitter -- Detecting Anomalies in Controlled Drug Prescription Data Using Probabilistic Models -- Multi-Phase Feature Representation Learning for Neurodegenerative Disease Diagnosis -- A Modified Case-Based Reasoning Approach for Triaging Psychiatric Patients Using a Similarity Measure Derived from Orthogonal Vector Projection -- The MST-kNN with Paracliques -- Mechanical Generation of Networks with Surplus Complexity -- Efficient Sensitivity Analysis of Reliability in Embedded Software -- Identifying Verb-Preposition Multi-Category Words in Chinese-English Patent Machine Translation -- Wavelet Based Artificial Intelligence Approaches for Prediction of Hydrological Time Series -- Ranking-Based Vocabulary Pruning in Bag-of-Features for Image Retrieval.
Keywords: Artificial intelligence; Computer science; Computer software; Computer Communication Networks; Optical pattern recognition; Artificial Intelligence; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Computer Communication Networks; Pattern Recognition